Dissemination, Health Features, Production and Agriculture of Turkestan Lion Plants in The Territory of Uzbekistan. - S.A.Misirov; A.M. Islamov (Universitas Muhammadiyah Sidoarjo, 2019)
The article describes the species of mammalian lion, which is widespread in Uzbekistan and describes its use in folk medicine, chemical composition, the use of herbal remedies in modern medicine, and the ways of preserving the natural resources of cultivating the Turkestan lion.